Nonresponsiveness and Susceptibility of Opioid Side Effects Related to Cancer Patients' Clinical Characteristics: A Post‐Hoc Analysis. Issue 6 (17th January 2018) - Corli, Oscar; Roberto, Anna; Bennett, Michael I.; Galli, Francesca; Corsi, Nicole; Rulli, Eliana; Antonione, Raffaella
Abstract: Background: The response to opioids is not always positive in cancer patients. A considerable proportion of patients do not respond (nonresponders [NRs]) or experience severe toxicity. The aim of this analysis was to assess the role of demographic characteristics, pain features, comorbidities, and ongoing therapy on the lack of efficacy and on the occurrence of severe adverse drug reactions (ADRs). Methods: This is a post‐hoc analysis of a randomized controlled trial that involved 520 patients and aimed to evaluate the efficacy and safety of 4 strong opioids. Patients who presented with unchanged or worsened pain compared to the first visit were considered to be NRs. As for toxicity, severe ADRs with an incidence of greater than 10% were evaluated. Univariate and multivariate logistic models were used. Results: 498 patients were analyzed. Liver metastases and breakthrough pain (BTP) were found to increase the risk for nonresponse. Conversely, a high basal pain intensity significantly decreased the same risk. Constipation risk was worsened by previous weak opioid therapy but decreased with aging and with the use of transdermal opioids. Risk for drowsiness was aggravated by bone metastases and concomitant treatment with anticoagulant, antidiabetic, and central nervous system drugs. Risk for confusion increased with antidiabetics, antibiotics, and previous weak opioid therapy but decreased when fentanyl was used. Occurrence of nausea increased in patients with a high rating on the Karnofsky Performance Status Index. Risk for xerostomia was higher in women and in patients treated with antidiabetic or long‐term opioids. Conclusions: Several clinical variables are correlated with opioid response in cancer patients. In particular, the presence of BTP is associated with nonresponse. Additionally, patients who receive polypharmacological therapy are more likely to experience opioid adverse events.